2018
DOI: 10.1155/2018/6413172
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Function as Anti-Inflammatory Agents in a Drosophila Model for Adipose Tissue Macrophage Infiltration

Abstract: Epidemiological and preclinical studies have demonstrated that bioactive foods like flavonoids, polyphenolic compounds derived from fruits and vegetables, exert a protective action against obesity, cardiovascular disorders, and Adipocyte Tissue Macrophage infiltration (ATM). All these pathologies are characterized by increase in reactive oxygen species (ROS) and in proinflammatory cytokines that have been shown to favor the migration of immune cells, particularly of macrophages, in metabolically active organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 54 publications
1
28
0
2
Order By: Relevance
“…A study using Drosophila model has shown antioxidant activity of anthocyanins . In this study, anthocyanin‐rich purple corn extract reduced the number of hemocytes (macrophages) in Drosophila after 12 days of supplementation, which is associated with the reduced levels of ROS by anthocyanin, which in turn inhibits the activation of JNK/SAPK p46 stress kinase . Supporting these findings, our recently published results also indicate that tart cherry anthocyanin can increase the antioxidant gene expression levels, such as nuclear factor erythroid 2–related factor 2 (NRF2), in epididymal adipose tissue of tart cherry (4% w/w) fed Zucker fatty rats for 8 weeks compared to control non‐supplemented rats …”
Section: Adipose Tissue Inflammation and Obesitysupporting
confidence: 74%
See 2 more Smart Citations
“…A study using Drosophila model has shown antioxidant activity of anthocyanins . In this study, anthocyanin‐rich purple corn extract reduced the number of hemocytes (macrophages) in Drosophila after 12 days of supplementation, which is associated with the reduced levels of ROS by anthocyanin, which in turn inhibits the activation of JNK/SAPK p46 stress kinase . Supporting these findings, our recently published results also indicate that tart cherry anthocyanin can increase the antioxidant gene expression levels, such as nuclear factor erythroid 2–related factor 2 (NRF2), in epididymal adipose tissue of tart cherry (4% w/w) fed Zucker fatty rats for 8 weeks compared to control non‐supplemented rats …”
Section: Adipose Tissue Inflammation and Obesitysupporting
confidence: 74%
“…[59] In this study, anthocyanin-rich purple corn extract reduced the number of hemocytes (macrophages) in Drosophila after 12 days of supplementation, which is associated with the reduced levels of ROS by anthocyanin, which in turn inhibits the activation of JNK/SAPK p46 stress kinase. [59] Supporting these findings, our recently published results also indicate that tart cherry anthocyanin can increase the antioxidant gene expression levels, such as nuclear factor erythroid 2related factor 2 (NRF2), in epididymal adipose tissue of tart cherry (4% w/w) fed Zucker fatty rats for 8 weeks compared to control non-supplemented rats. [60] To understand the effects of anthocyanin-containing fruits, it is important to compare the effects of whole fruit extracts or powder to purified anthocyanins on obesity and other metabolic alterations.…”
Section: Animal Studies and Model Organismsmentioning
confidence: 64%
See 1 more Smart Citation
“…The role of the inflammatory response to combat infection and tissue injury, through the activation of the immune cells, is conserved also in Drosophila's circulating hemocytes (Lemaitre and Hoffmann, 2007), where most of the signals activated in the fat body results also in ROS production (Dionne, 2014; Vlisidou and Wood, 2015). Indeed, we showed, using a genetic model that harbors an inflammation state in the fat body of larvae that mimic ATM, that reduction of ROS, using exogenous anti-oxidants components like flavonoids and anthiocianins, decreased hemocyte's migration and JNK activation in the cells of fat body (Valenza et al, 2018), suggesting that the converging signaling between the fat body and hemocytes on lipid metabolism and ROS/cytokines in response to stress is conserved also in Drosophila .…”
Section: Cancer and Lipid Metabolism Obesitymentioning
confidence: 99%
“…Our second compound of interest is tart cherry anthocyanins (TCA), also known for their anti-inflammatory and antioxidant effects [21][22][23][24][25][26][27]. Anthocyanins belong to the flavonoid group and mostly found in fruits and vegetables [21,24].…”
Section: Introductionmentioning
confidence: 99%